1970
DOI: 10.1042/bj1190323
|View full text |Cite
|
Sign up to set email alerts
|

Competing addition and hydrolysis of the cytidylylcytidylyladenosine terminal residues of transfer ribonucleic acid isolated from the non-lactating bovine mammary gland

Abstract: 1. The enzyme fraction obtained from the pH5 enzyme of non-lactating bovine mammary gland between 40 and 100% ammonium sulphate saturation markedly inhibited the AMP-incorporating activity of rat liver nucleotide-incorporating enzyme. This inhibitory effect has been attributed to high nuclease activity which can be partially removed by adsorption of the enzyme fraction on to calcium phosphate gel. 2. The degradation action of the calcium phosphate-purified enzyme is confined mainly to the terminal trinucleotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1973
1973
1988
1988

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…It is known that addition of tRNA can lead to inhibition of the incorporation of amino acids in protein-synthesizing systems (Herrington & Hawtrey, 1970b). A significant feature here, however, is that tRNA isolated from the pH5 enzyme fraction from myopathic muscle had no stimulatory effect in both systems studied (Table 1), although it could be aminoacylated to a certain extent (Fig.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…It is known that addition of tRNA can lead to inhibition of the incorporation of amino acids in protein-synthesizing systems (Herrington & Hawtrey, 1970b). A significant feature here, however, is that tRNA isolated from the pH5 enzyme fraction from myopathic muscle had no stimulatory effect in both systems studied (Table 1), although it could be aminoacylated to a certain extent (Fig.…”
Section: Resultsmentioning
confidence: 67%
“…1). Herrington & Hawtrey (1970b) showed that bovine tRNA, lacking the terminal -pC-C-A-OH trinucleotide group, competitively inhibits the aminoacylation of rat liver tRNA. On the other hand, when the terminal -pC-C-A-OH group has been added the material stimulates the synthesis of rat liver aminoacyl-tRNA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This enzyme has been extensively purified and studied in Escherichia coli (Carre et al, 1970), and it has been found in 55-85 % ammonium sulfate saturated fractions from rat liver (Herbert and Canellakis, 1963). The enzyme is active under the conditions of the aminoacylation assay (Herrington and Hawtrey, 1970) and the addition of CTP to reaction mixtures provides conditions suitable to the repair of tRNAs deficient at the CpCpA-OH terminus. The addition of CTP to reaction mixtures, and therefore the repair of deficient pCpCpA-OH termini, does not significantly increase the extent of liver phenylalanyl-tRNA formation, much less increase it to the level obtainable with hepatoma tRNA.…”
Section: Resultsmentioning
confidence: 99%